III.i. Letters to the Rev. Richard Wolfe, concerning business and political matters - O'Brien-Stafford, Augustus Stafford; Peel, Robert, 1788-1850; Wolfe, Richard, Rev., 1787-1841; Carysfort, John Joshua Proby, Earl of, 1751-1828; Mayo, John Bourke, Earl of, 1766-1849; De Roebeck, John Henry Fock, Baron, 1753-1817 (1817)
Letters to the Rev. Richard Wolfe of Forenaughts, Co. Kildare, from assorted correspondents, largely concerning official, business and political matters. Includes letters from Robert Peel, then Chief Secretary for Ireland, concerning the Lord Lieutenant's influence in relation to Church of Ireland appointments (21 Jan. 1817), Countess Nugent, concerning financial matters (6 Dec. 1822), Daniel Byrne, concerning financial matters (6 Nov. 1823), John, Baron de Robeck, concerning the Naas Savings Bank (1824), Lord Mayo, concerning financial matters (27 Feb. 1826) and a mimeograph letter from politician Augustus Stafford O'Brien-Stafford, requesting support in the forthcoming election (28 Jul. 1837).
Also included is a letter to John Proby, Earl of Caryfort, concerning the leasing of lands in Tipper. The letter, written from Forenaughts and dated 5 Feb. 1817, was most probably written by Wolfe.
Keywords: Wolfe, Richard, -- Rev., -- 1787-1841